Late cardiac adverse events in patients with cancer treated with immune checkpoint inhibitors - Charles Dolladille; Joachim Alexandre; Radj Gervais; Stéphane Allouche; Querntin Dupas; Jeannick Madelaine; Anne-Flore Plane; Francois Comoz; Ariel Aron Cohen; Franck Roland Thuny (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitor (ICI)-associated early cardiac adverse events (CAEs), mostly acute and fulminant myocarditis, have been well characterized and mainly occur during the first 90 days after ICI therapy initiation. ICI-associated late CAEs (occurring after the first 90 days of treatment) have not yet been described.Methods First, we compared characteristics of a cohort involving early (defined as a CAE time to onset (TTO) of <90 days after ICI therapy initiation) and late (defined as a CAE TTO of ≥90 days after ICI therapy initiation) ICI-associated CAE consecutive cases who were referred to three French cardio-oncology units. Second, ICI-associated CAE cases were searched in VigiBase, the WHO global individual case safety report database, and early and late ICI-associated CAEs were compared.Results In the cohort study, compared with early CAE cases (n=19, median TTO of 14 days), late ICI-associated CAE cases (n=19, median TTO of 304 days) exhibited significantly more left ventricular systolic dysfunction (LVSD) and heart failure (HF) and less frequent supraventricular arrhythmias. In VigiBase, compared with early cases (n=437, 73.3%, median TTO 21 days), the late ICI-associated CAE reports (n=159, 26.7%, median TTO 178 days) had significantly more frequent HF (21.1% vs 31.4%, respectively, p=0.01). Early and late ICI-associated CAE cases had similarly high mortality rates (40.0% vs 44.4% in the cohort and 30.0% vs 27.0% in VigiBase, respectively).Conclusions Late CAEs could occur with ICI therapy and were mainly revealed to be HF with LVSD.Trial registration numbers NCT03678337, NCT03882580, and NCT03492528.